Creep evolution characteristics and deformation mechanisms of carbonaceous slate under the action of groundwater - Hucheng Yang; Peng Li; Shengrui Su; Jianxun Chen (Scientific Reports)
Abstract The carbonaceous slate exhibits significant creep characteristics and large deformations during tunnel excavation, especially in groundwater-rich areas. Studying the creep characteristics and deformation mechanism of carbonaceous slate under the influence of groundwater is substantial and essential. Triaxial creep tests of dry and saturated rock samples at different bedding angles were performed to examine the deformation characteristics using the GCTS-RTX1000 test system. The layered surface morphology was analyzed before and after the creep to reveal the deformation mechanisms. The results showed that the softening effect of water causes a significant reduction in the strength of the carbonaceous slates. The transient deformation of saturated samples was greater than that of dry samples due to the water absorption in the pores at a low-stress state. Creep in the saturated rock samples is more pronounced in the first stage compared to the dry samples, and the gap decreases as the stress increases. In the creep processes, the saturated samples manifested the pressure dissolution, debris migration, and deposition in the stratified surface of the particle skeleton under the water and the stress. These results are helpful for better understanding the creep characteristics of the carbonaceous slate in water-rich areas.